Citrobacter freundii, a natural associate of the Colorado potato beetle, increases larval susceptibility to Bacillus thuringiensis - Polenogova, Olga V.; Noskov, Yury A.; Artemchenko, Anna S.; Zhangissina, Saule; Klementeva, Tatyana N.; Yaroslavtseva, Olga N.; Khodyrev, Viktor P.; Kruykova, Natalya A.; Glupov, Viktor V. (Pest management science)
BACKGROUND We assume that certain representatives of gut microflora mediate immune changes during dysbiosis, accelerating septicemia caused by Bacillus thuringiensis. RESULTS Co-introduction of Citrobacter freundii with Bacillus thuringiensis var. tenebrionis (morrisoni) (Bt) led to an increase in Colorado potato beetle (CPB) larval mortality to 69.0% (1.3-5x) and a synergistic effect was observed from day 1 to day 6. Ultrathin sections of the CPB midgut showed autophagosome formation and partial destruction of gut microvilli under the influence of Bt, which was accompanied by pronounced hypersecretion of the endoplasmic reticulum with apocrine vesicle formation and oncotic changes in cells under the action of C. freundii. The destruction of gut tissues was accompanied by suppression of detoxification processes under the action of the bacteria and a decrease (2.8-3.5x) in the concentration of lipid oxidation products during Bt infection. In the first hours post combined treatment, we registered a slight increase in the total hemocyte count (THC) especially a predomination (1.4x) of immune-competent plasmatocytes. Oral administration of symbiotic and entomopathogenic bacteria to the CPB larvae significantly decreased the THC (1.4x) after 24 h and increased (1.1-1.5x) the detoxifying enzymes level in the lymph. These changes are likely to be associated with the destruction of hemocytes and the need to remove the toxic products of reactive oxygen species. CONCLUSION The obtained results indicate that feeding of C. freundii and B. thuringiensis to the CPB larvae is accompanied by tissue changes that significantly affect the cellular and humoral immunity of the insect, increasing its susceptibility to Bt.